PENERAPAN PARIWISATA BERBASIS MASYARAKAT DI THE KALDERA TOBA NOMADIC ESCAPE, KABUPATEN TOBA, SUMATERA UTARA - Yosinda Delani Silalahi; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
This study aims to describe the implementation of community-based tourism at The Kaldera Toba Nomadic Escape, Toba Regency, North Sumatra. The study focuses on stakeholder support for community empowerment, community empowerment in tourism development, and community involvement in the tourism life cycle. A qualitative approach with an inductive method was applied. Data were collected through interviews, observation, and documentation, and analyzed through data reduction, data display, and conclusion drawing and verification. The findings show that community-based tourism has been implemented at The Kaldera, but not yet optimally. Stakeholder support is reflected in training, facilitation, and communication channels for local communities. Community empowerment is seen in the involvement of local people in MSMEs, cultural arts, security, cleaning services, guiding, and culinary businesses. However, community involvement in the tourism life cycle remains limited to operational stages and is still weak in strategic decision-making. Therefore, The Kaldera Toba Nomadic Escape has applied community-based tourism principles, but stronger community participation is still needed to achieve a more authentic and sustainable model.